Good Governance in Indonesian Administrative Law: Integrating General Principles and Accountability of Governmental Authority - Ery Setyanegara; Novekawati (BRIDGE : The Multidisciplinary Research Portal, 2026)
This article examines good governance as a legal standard for controlling governmental authority in Indonesian administrative law. It addresses the persistent gap between extensive statutory recognition of legality, transparency, accountability, public service, and the General Principles of Good Governance (AUPB) and the continuing risks of maladministration and abuse of authority. Using normative legal research, the study combines statutory, conceptual, and case approaches. Primary legal materials include the 1945 Constitution, Law No. 28 of 1999, Law No. 14 of 2008, Law No. 25 of 2009, Law No. 37 of 2008, and Law No. 30 of 2014 as amended by Law No. 6 of 2023, together with Constitutional Court Decision No. 66/PUU-XXIV/2026. The analysis finds that good governance has evolved from an administrative management doctrine into a legally enforceable framework operating through four interrelated layers: legality and AUPB as standards for governmental action; transparency and participation as mechanisms of public scrutiny; public-service obligations as direct guarantees for citizens; and administrative and judicial accountability as corrective controls. Decision No. 66/PUU-XXIV/2026 further strengthens legal certainty by interpreting the phrase "state loss" in Article 20(5) and (6) of the Government Administration Law as "state financial loss." The article argues that effective good governance requires integration across these layers rather than fragmented compliance with individual principles. This integrated framework is especially relevant to digital government, where efficiency must remain consistent with legality, explainability, accountability, and the protection of citizens' rights.